Inovasi Pemberdayaan Usaha Mikro Kecil Kerajinan Eceng Gondok melalui Digital Marketing - Kurniawan, Bachtiar Dwi; Fitriyani, Alni; Kurniawati, Nawang (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2024)
Purpose – The purpose of this community service activity is to provide education to the residents of Dusun Tapen, especially the Water Hyacinth Craftsmen of Cempaka Tapen, to enhance the digital marketing of their products. In this activity, we also aim to encourage the local government to support Cempaka Tapen's handicraft business so that it can become a Village-Owned Enterprise (BUMDES) and further advance and develop. Design/methodology/approach – This community service activity consists of several stages of activities: (1) Observation, using interview and field survey methods; (2) Formulation of activities, as a follow-up to the observation; (3) Dissemination/Socialization to the residents; and (4) Facilitation of infrastructure and facility assistance. Findings – The impact of implementing this activity is the establishment of social media accounts for Cempaka Tapen's SMEs. Entrepreneurs can operate social media effectively, and engagement with these SMEs has increased. Additionally, the local government has begun considering the establishment of a BUMDES, even though the results are not yet visible. Originality/value - The originality of this activity is in the research object and location. This activity focuses on the capacity development of human resources in Cempaka Tapen's SMEs, as one of the SMEs in Dusun Tapen, to introduce digital marketing and apply it to the sales process.